Transforming Spent Coffee Grounds’ Hydrolysates with Yeast Lachancea thermotolerans and Lactic Acid Bacterium Lactiplantibacillus plantarum to Develop Potential Novel Alcoholic Beverages - Yunjiao Liu; Yuyun Lu; Shao-Quan Liu (Foods, 2023)
In the present work, the modification of spent coffee grounds (SCG) hydrolysate composition by mixed cultures of a non-Saccharomyces yeast, Lachancea thermotolerans, and a lactic acid bacterium, Lactiplantibacillus plantarum, as well as their interactions, were evaluated. It was found that L. plantarum inhibited the growth and survival of L. thermotolerans as compared with that in the yeast alone. On the other hand, the growth and survival of L. plantarum was slowed in sequential fermentation, but not in co-culture. Compared with co-culture, higher ethanol content, less residual sugars, and less acetic and succinic acids were found in sequential fermentation. In addition, lower amounts of caffeine and phenolic acids (e.g., ferulic, caffeic, and p-coumaric acids) were obtained in mixed (co- and sequential) cultures with corresponding levels of volatile phenols relative to the yeast monoculture. Moreover, co-culturing resulted in the highest contents of total alcohols (ethanol excluded) and total esters. Therefore, mixed culturing of L. plantarum and L. thermotolerans presented positive effects on the chemical constituents of fermented SCG hydrolysates, which might be a new alternative approach to valorizing the SCG into novel alcoholic drinks with different ethanol and flavor constituents.